Does CEO’s Financial Decision Able To Improve Firm Value Of Consumer Good Industry - Widya Sari; Darni Waruwu; Ewnike Purba (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of PER, DER, and DPR financial decisions with CEO as a moderating variable on firm value in the consumer goods industry in 2015-2019. The researcher uses a quantitative approach with quantitative descriptive research and explanatory research. Collecting sample data using purposive sampling method, with the help of software SPSS to do testing statistic analysis. From the results of this study the researchers found that partially, investment decisions have a positive influence in increasing firm value, with the CEO having a positive influence on investment decisions in increasing firm value. And simultaneously Investment Decisions, Funding Decisions, and Dividend Decisions affect the value of the company, with the CEO influencing the three financial decisions on the value of consumer goods industry companies listed on the Indonesia Stock Exchange. with the CEO who has a positive influence on financial decisions on firm value, then it becomes a difference to previous research that has been done on firm value.